Readiness for Accreditation of the Administration and Management Working Group at the Basaan Community Health Center Southeast Minahasa Regency - Wijayanti, Lumastari Ajeng; Lestaluhu, Viqy; Saputra, M. Khalid Fredy; Masithah, St.; Pannyiwi, Rahmat; Malaha, Naomi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The policy implemented by the Ministry of Health in an effort to improve the quality of services at first level health facilities, especially Community Health Centers, is to issue Regulation of the Minister of Health (Permenkes) of the Republic of Indonesia Number 46 of 2015 concerning Accreditation of Community Health Centers, Primary Clinics, Doctors' Independent Practice Places, and Doctors' Independent Practice Places. Tooth. The aim of the research is to describe the readiness for accreditation of the administration and management working group at the Basaan Community Health Center, Southeast Minahasa Regency. This type of research is qualitative research with a case study approach. The results of the research show that the Basaan Community Health Center for the Community Health Center Administration and Management Working Group in terms of Quality Improvement of the Community Health Center is ready for accreditation based on Community Health Center accreditation standards. The conclusion is that the Basaan Community Health Center for the Community Health Center Administration and Management Working Group in terms of Puskesmas Quality Improvement (PMP) is ready for accreditation based on community health center quality improvement standards.